Pinocchio [videorecording (DVD)] - Garrone, Matteo, 1968-; Garrone, Matteo, 1968-; Garrone, Matteo, 1968-; Ielapi, Federico; Benigni, Roberto; Papaleo, Rocco, 1958-; Collodi, Carlo, 1826-1890 (Samuel Golwyn Films, 2021)
A poor, lonely carpenter longing for a real son carves a wooden puppet who magically comes to life.